La potestad disciplinaria del Consejo de la Judicatura que vulnera el principio de independencia judicial - Redrobán Portalanza, Natalia Stephanie (2017)
As a guarantee of the constitutional rights that the States of Law must provide to their citizens, there is respect for the separation of powers. The structure that conforms this principle is the independence and the respect to each state function. Nevertheless, throughout history has been maintaining a constant struggle for such respect to be fully respected, in such a way that none of these powers bursts the other affecting the independence that characterizes them, and for this reason the rights of citizens are affected. As Montesquieu states in his theory of division of powers, the State must have three functions, one executive, one legislative and a judicial, to which certain functions will be assigned according to the area that they must control and guarantee. Of the Judicial Power, which is the object of this work, it shows that it is a power that is invisible and separated from the other powers, since it is in charge of the administration of justice of conflicts that are generated in its territory and that no power outside the Judicial Function should intervene in the decisions that the judges take. Is for this reason that a Judiciary Council is established legally with the purpose that a single organ, outside the other functions of the State, is responsible for the government and administration of the Judicial Function, which within its functions is responsible of the selection, assent, stability, removal and discipline of judges and judicial servers, in the margin of the administrative scope. That is to say, the Judiciary Council should exercise its disciplinary authority, regulation and control over the behavior that judges keep on the Judicial Function, and not on the decisions made by them, otherwise, the principle of judicial independence would be affected.